A generalization of the Ricets distribution - Sarabia, José (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we generalize the Rice's random variable. We calculate the m-th moment, the distribution function, the characteristic function, the mode and the distribution of the products of Rice's -(a, a, v) random variables.